Epidemiology and outcomes of hyphema: a single tertiary centre experience of 180 cases. Issue 3 (29th October 2020) - Iftikhar, Mustafa; Mir, Tahreem; Seidel, Natalie; Rice, Katya; Trang, Michelle; Bhowmik, Ryan; Chun, Justin; Goldberg, Morton F.; Woreta, Fasika A.
Abstract: Purpose: To characterize the epidemiology and outcomes of hyphema. Methods: Retrospective case series. Medical records from patients with traumatic and spontaneous hyphema seen at the Wilmer Eye Institute, Johns Hopkins, from 2011 through 2017 were evaluated. Aetiology, demographics, clinical characteristics, complications, management and outcomes were ascertained. Multivariable logistic regression was used to identify factors associated with elevated intraocular pressure (IOP), rebleeding and poor outcome (final visual acuity ≤ 20/40) in traumatic hyphema. A safe frequency of follow‐up was retrospectively determined. Results: Traumatic hyphema ( n = 152) was more common in males (78%) and adults (55%), with sports/recreational activities being the most frequent cause (40%). Elevated IOP was the most common complication (39%). Rebleeding occurred in seven patients (5%) and was more likely with a higher IOP on presentation (OR:1.1; p = 0.004). Thirty‐seven patients (24%) had a poor outcome, mostly due to traumatic sequelae such as cataract (32%) or posterior segment involvement (30%). A poor outcome was more likely with worse presenting visual acuity (OR: 9.1; p = 0.001), rebleeding (OR: 37.5; p = 0.035) and age > 60 years (OR: 16.0; p = 0.041). Spontaneous hyphema ( n = 28) did not have a gender predominance and was more common in adults > 60 years (71%). The most common cause was iris neovascularization (61%). Complications and visual outcomes were worse compared with traumatic hyphema. Conclusions: Traumatic hyphema continues to be common in young males engaging in sports, necessitating increased awareness for preventive eyewear. Older age and rebleeding can lead to poor outcomes. Elevated IOP at presentation predisposes to rebleeding and warrants frequent follow‐up. Otherwise, routine follow‐up at days 1, 3, 5, 7 and 14 is sufficient for uncomplicated cases.